Adopting a photo-sharing site as a library tool: a web-based survey - De Sarkar, Tanmay (Information and learning science, 2017)
Purpose The study demonstrates how libraries are incorporating photo-sharing applications into the collection development and service provision to encourage improved user participation around digital inclusion. Investigating the steps to increase accessibility to photo-sharing sites and current photo-sharing practices, the paper seeks to highlight the extent of implementation across the world. Design/methodology/approach Stratified sampling method was used to select libraries from four continents. Content analysis was used to collect data from 160 libraries along the lines of evaluation models prepared for the purpose. Findings With the comparative account of implementation of photo-sharing apps, the study showcases the relevance of different approaches adopted by libraries and also presents an overview of the implementation with supportive examples. Research limitations/implications The present investigation is limited to selected libraries of four continents and restricted to English websites only. The study may further be extended to include other types of libraries in different areas, including libraries using non-English websites, to get a fuller picture of implementation. Originality/value The paper makes an attempt to improve the understanding of the budding library professionals toward the usage pattern of photo-sharing sites. The guidelines, based on a brief synthesis of the functions/purposes of photo-sharing sites, will make a stronger case for the implications of this research to future photo-sharing practices.